Implementasi Artificial Intelligence (AI) Dalam Proses Perubahan Konstitusi dan Implikasinya - Darmawan, Abqary Faraz; Triadi, Irwan (Media Hukum Indonesia (MHI), 2024)
Developments over time continue to occur and the constitution itself often evolves with the times, so it is necessary to draft a "living" constitution, namely one that can keep up with the times and adapt to the needs of society. In general, the constitution is a guideline that regulates the running of the government, limits power, and guarantees human rights so that the government does not act arbitrarily. With the rapid development of technology in this day and age, technology such as Artificial Intelligence (AI) is starting to emerge, and so new ideas are emerging to facilitate the process of changing the constitution, namely by implementing AI. From there, questions arise such as how AI can be implemented into the constitutional change process and its implication. This article uses normative juridical methods by studying documents or literature. This research is based on several approaches, namely the conceptual approach, the statutory approach and the historical approach. With the application of Machine Learning for AI, it will be possible to implement AI in constitutional changes. AI will provide ideas and recommendations for changes to regulations that are felt to be no longer in line with people's aspirations. AI can also provide an overview of the impact of the changes to be made. Apart from that, AI will supervise changes to the constitution. The implementation of AI in constitutional change has significant implications, one of which is making the constitutional change process more efficient.